2014
DOI: 10.1089/zeb.2013.0917
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gut Microbiota in a Zebrafish Model with Chemically Induced Enterocolitis Involving Toll-Like Receptor Signaling Pathways

Abstract: Background/Aims: It is believed that inflammatory bowel disease (IBD) involves a breakdown in interactions between the resident commensal microbiota and the host immune response. Recent studies have revealed that gut physiology and pathology relevant to human IBD can be rapidly modeled in zebrafish larvae with a number of advantages compared with murine models. The objective of this study was to evaluate the role of gut microbiota in zebrafish models with IBD-like enterocolitis. Methods: IBD-like enterocolitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 45 publications
(53 reference statements)
1
21
0
3
Order By: Relevance
“…Previous zebrafish-based studies have reported an increase in gene expression of IL-1β and TNF-α in adult fish few hours after they had been exposed to oxazolone [6] or TNBS [10]. Similar increases have been reported using larval TNBS-models and qPCR/immunofluorescence techniques [7] [9] [11]. The role of IL-6 has not been scrutinized in colitis models using zebrafish until now.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Previous zebrafish-based studies have reported an increase in gene expression of IL-1β and TNF-α in adult fish few hours after they had been exposed to oxazolone [6] or TNBS [10]. Similar increases have been reported using larval TNBS-models and qPCR/immunofluorescence techniques [7] [9] [11]. The role of IL-6 has not been scrutinized in colitis models using zebrafish until now.…”
Section: Discussionmentioning
confidence: 84%
“…TLR orthologs as well as MyD88 signalling and NF-κb activation have been described from larval zebrafish [50] [51]. Recently, He et al [11] reported an increase of TLR-3, the signaling proteins MyD88 and TICAM-1(TRIF) and NF-κb in TNBS-treated zebrafish larvae. This is in contrast with the results obtained in the present study in which only TLR-2 and TICAM-1 were significantly down-and up-regulated in the oxazolone group after 72 h and in the TNBS group after 6 hpi, respectively; TLR-3, MYD88 and NF-κb were not significantly affected by the chemical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although mouse models of IBD have been used for more than 20 years and have been instrumental in defining many of the major immunopathological mechanisms responsible for inflammatory tissue injury in these models, progress as been slow for reasons outlined above [95]. Thus, several groups of investigators have turned to the use of zebrafish to model IBD (see below) [19,47,63,64,216]. The objective of this review is to present our current understanding of the role that the intestinal microbiota play in vertebrate intestinal health and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Во-первых, имеются доказательства активации кишечной иммунной системы при СРК, которая приводит к микровоспалению, в исследо-ваниях, демонстрирующих повышенные концентрации лимфоцитов в слизистых оболочках [31], тучных клетках [32,33] и 5-гидрокситриптамин-секретирующих энтерох-ромаффинных клетках [34]. Исследования на живот-ных подчеркивают критическую роль микрофлоры кишеч-ника в балансе между иммуносупрессией и воспалением в желудочно-кишечном тракте, включая Toll-подобные рецепторы (TLRs) сигнальных путей [35]. Во-вторых, при-близительно у 10% пациентов с СРК симптомы начались после эпизода инфекционной диареи [36,37], т. н. постин-фекционный СРК (ПИ-СРК).…”
unclassified